The Influence of Training, Motivation, and Self-Efficacy on Career Planning - Sri Martini; Waqar Akbar Khan; Ani Muttaqiyathun (Jurnal Genesis Indonesia, 2023)
This research study was conducted to investigate the influence of training, motivation, and self-efficacy on career planning among final year students of the Management Study Program. The main purpose of this research was to determine whether these three variables had any significant effect on the student's career planning. The research design used in this study was quantitative and correlational. Purposive sampling was used to select the participants of this study, with a total of 128 students being selected. The statistical techniques used included multiple linear regression, T-test, and F-test. The results of the study showed that the variables of training, motivation, and self-efficacy collectively have a significant influence on the career planning of final year students in the Management Study Program. Additionally, it was found that the variables of training, motivation, and self-efficacy individually have a significant positive effect on career planning. These findings suggest that students who receive adequate training, have high levels of motivation, and possess a strong sense of self-efficacy are more likely to engage in career planning activities.